Connectivity in higher education, from the perspective of equality. The case of the Universities in México during the covid-19 pandemic - Castro Coria, Eva Grissel (2021)
The objective is to study how the delivery of digital goods and services materializes human rights, especially the right to education, with the intention of reversing the digital divide. For this reason, the methodology aims to identify: How digital goods and services were granted, to promote better levels of connectivity and thereby promote the teaching and learning process, at higher education levels during the covid-19 pandemic? Consequently, the technique employed to collect the information adhered to the right of access to information, and as an instrument a questionnaire was sent to 35 autonomous public universities in Mexico, whose responses were transformed into a dichotomous variable, dynamic tables and personalized graphs. The main results refer that the delivery of digital educational goods and services was granted under conditions of equity, giving to some, but not to others. For this reason, the conclusions identify how the UPAS expand their portfolio of educational platforms and digital tools to give continuity to educational processes, in the face of an evident context of digital inequalities.